Studies on Canopy Parameters of Some Mangroves Along the Coast of Maharashtra - Kulkarni, N A; Bhosale, L J (Plantae Scientia, 2021)
Mangrove species, viz., Avicennia officinalis, Avicennia marina var. acutissima, Avicennia marina (dwarf), Rhizophora mucronata, Sonneratia alba, Aegiceras corniculatum, Kandelia candel were chosen for measurement of height of the tree and girth or circumference. The sampling was random and at least 50 records were made. The girth is measured by the tape. The measurement of the height is made with the help of Abney level. The Tables 1 to 8 records the values for girth, height and canopy cover as well as for correlation coefficient (r). There correlation between girth and canopy in all the species studied however in case of Avicennia officinalis and Aegiceras corniculatum girth and height show more co-relation than girth and C. cover. The positive co-relation observed between girth and canopy is more or less 0.7 except Avicennia marina (dwarf) Excoecaria agallocha and Aegiceras corniculatum. The co-relation is observed in girth and height is difficult to explain. This case is observed in Avicennia officinalis and Aegiceras corniculatum.